Polarity determination in breast tissue: desmosomal adhesion, myoepithelial cells, and laminin 1 - Bissell, Mina J (BioMed Central, 2003)
In all epithelial organs, apicobasal polarity determines functional integrity and contributes to the maintenance of tissue and organ specificity. In the breast, the functional unit is a polar double-layered tube consisting of luminal epithelial cells surrounded by myoepithelial cells and a basement membrane. It is far from clear how this double-layered structure is established and how polarity is maintained. Two recent papers have shed some light onto this intriguing problem in mammary gland biology. The results point to desmosomes and laminin 1 as having crucial roles. However, some questions remain.